KAJIAN YURIDIS UNDANG-UNDANG REPUBLIK Indonesia NOMOR 36 TAHUN 2008 TENTANG PAJAK PENGHASILAN (PPH) TERKAIT PEMBUKTIAN PEMBAYARAN PAJAK ENDORSEMENT INFLUENCER TIKTOK - Wardani, Ni Putu Mahadewi Niken Ayu; Suharyanti, Ni Putu Noni (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Tax is a very important income for the balance of state revenue. This research aims to discuss the tax system applied to Influencer TikTok, especially in the endorse activity business. This research uses an analytical descriptive method by collecting several sources of literacy and discussing them in paragraph form. Taxes in Indonesia itself are increasingly developing where the system follows the development of online technology. Social media these days is starting to become a business field for influencers or celebrities. Endorse activities are a way for them to earn income. Thus, the income tax system allows them to pay taxes. self- assessment can be a way to pay taxes independently that makes it easier for them. In Indonesia, if taxpayer do not pay, they will be subject to criminal law and fines. Of course, the job of a celebrity in Indonesia is a job that provides a large income that must be taxed. In fact, there are still many influencers, who are not tax compliant due to a lack of education on income tax.